Distance Control and Virtual Drilling Improves Anatomical Orientation During Anterior Petrosectomy. Issue 1 (24th April 2019) - Voormolen, Eduard H; Diederen, Sander; Cebula, Helene; Woerdeman, Peter A; Noordmans, Herke Jan; Viergever, Max A; Robe, Pierre A; Froelich, Sebastien; Regli, Luca; Berkelbach van der Sprenkel, Jan Willem
Abstract: BACKGROUND: A combined drill distance control and virtual drilling image guidance feedback method was developed. OBJECTIVE: To investigate whether first-time usage of the proposed method, during anterior petrosectomy (AP), improves surgical orientation and surgical performance. The accuracy of virtual drilling and the clinical practicability of the method were also investigated. METHODS: In a simulated surgical setting using human cadavers, a trial was conducted with 5 expert skull base surgeons from 3 different hospitals. They performed 10 AP approaches, using either the feedback method or standard image guidance. Damage to critical structures was assessed. Operating time, drill cavity sizes, and proximity of postoperative drill cavities to the cochlea and the acoustic meatus, were measured. Questionnaires were obtained postoperatively. Errors in the virtual drill cavities as compared with actual postoperative cavities were calculated. In a clinical setup, the method was used during AP. RESULTS: Surgeons rated their intraoperative orientation significantly better with the feedback method compared with standard image guidance. During the cadaver trial, the cochlea was harmed on 1 occasion in the control group, while surgeons drilled closer to the cochlea and meatus without injuring them in the group using feedback. Virtual drilling under- and overestimation errors were 2.2 ± 0.2 and −3.0 ± 0.6 mm on average. The method functioned properly during the clinical setup. CONCLUSION: The proposed feedback method improves orientation and surgical performance in an experimental setting. Errors in virtual drilling reflect spatial errors of the image guidance system. The feedback method is clinically practicable during AP.